New Epigraphic Inscriptions from the Italian-Syrian Archaeological Mission of Palmyra (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2016)
The paper focuses on the Greek and Semitic inscriptions found during the excavation of the Peristyle Building in the south-west quarter of Palmyra, which was carried out by the Italian-Syrian archaeological joint mission Pal.M.A.I.S. between 2008 and 2010. The inscriptions, incised or painted on stone and pottery, add new interesting data on the historical development of the building, dated between the late 2nd - 3rd and the 8th centuries AD.
Keywords: Syria; Palmyra; Italian-Syrian Mission; inscriptions; Greek; Aramaic